Pengaruh Financing to Deposit Ratio (FDR), Non Performing Financing (NPF), dan Biaya Operasional Per Pendapatan Operasional (BOPO) terhadap Return On Asset (ROA) pada Bank Umum Syariah di Indonesia Periode 2015-2018 - Nidya Lestari; Peny Cahaya Azwari; Melis Melis (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2020)
This study aims to analyze the influence of Financing to Deposit Ratio (FDR), Non Performing Financing (NPF) and Operational Cost Per Operating Income (BOPO) on Return on Assets (ROA) of Islamic commercial banks in Indonesia for the 2015-2018 period. This study uses a purposive sampling method based on financial reports / annual reports (anual report) of Islamic commercial banks in Indonesia during the 2015-2018 period. There are 9 Islamic commercial banks and 36 financial statements that are sampled in this study. Based on the results of simultaneous research FDR, NPF and BOPO affect ROA of Islamic commercial banks. Partially, FDR has a positive and significant effect on ROA. The NPF variable has no effect on ROA. While BOPO has a negative and significant effect on ROA.